The causes, evolusion and environmental evaluation of sand dunes activity in Manisa-Akselendi plain. - Taysun, A.; Ozden, N.; Sahin Taysun, K.; Yilmaz, G.; Vassilopoulos, A.; Evelpidou, N. (Ulusal Kuraklik ve Collesme Sempoozyumu, 2009)
Inland sand dune activities that set an interesting example in terms of wind erosion and accummulation in the Aegean Region under the conditions of the Mediterranean climate, and that appear on lands where the annual rainfall is about 600 mm, exist on the Akselendi Plain, Manisa. Until today, some studies have been conducted on the Akselendi Plain, which has become famous worldwide for that matter. Besides, there is an ongoing Bilateral Project with GREECE, supported by TUBITAK, some results of which will be explained in this paper. Besides the erosive winds blowing on the Akselendi Plain, the existence of mostly coarse textured alluvial deposits, the first of which is the large bed of Kum Çayı, moreover, the misuse of agricultural and non-agricultural areas have caused wind erosion, and they also caused the sediments, moving from the bed of Kum Çayı by deflation, to give great damages along with the sand dune invasion in the south of the bed. This activity has especially increased in the last fifty years. The views that we reached on the subject of wind erosion on this area and the causes, evolution and effects of sand dunes will be reported in the paper. Moreover, information will be given on the problems and on the status and efficiency of the precautions that have been taken, besides on the precautions that will need to be taken in the short term and long term. Again, the continued sand plunder because of the incorrect applications, and the effects of that on the sand dune formation will be explained. Also, some interesting formations that we determined in the last studies we conducted and that can set an example in this scientific area will be submitted to the world of science.